Exposure to family stressful life events in autistic children: Longitudinal associations with mental health and the moderating role of cognitive flexibility. (October 2022) - Carter Leno, Virginia; Wright, Nicola; Pickles, Andrew; Bedford, Rachael; Zaidman-Zait, Anat; Kerns, Connor; Mirenda, Pat; Zwaigenbaum, Lonnie; Duku, Eric; Bennett, Teresa; Georgiades, Stelios; Smith, Isabel; et al.
Mental health problems are prevalent in autistic youth, but the underpinning mechanisms are not well explored. In neurotypical youth, stressful life events are an established risk factor for mental health problems. This study tested longitudinal bidirectional associations between family-level stressful life events and mental health problems and whether these were moderated by cognitive flexibility, in a cohort of autistic children ( N  = 247). Family-stressful life events, assessed using the parent-reported Family Inventory of Life Events and Changes, and mental health problems, assessed using the teacher-reported Child Behavior Checklist Internalizing and Externalizing Symptoms subscales, were measured at multiple points between 7 and 11 years. Analyses showed no significant pathways from internalizing or externalizing symptoms to family-stressful life events or from family-stressful life events to internalizing or externalizing symptoms. There was some evidence of moderation by cognitive flexibility; the family-stressful life events to internalizing symptoms pathway was non-significant in the group with typical shifting ability but significant in the group with clinically significant shifting problems. Information about family-level stressful life event exposure and cognitive flexibility may be helpful in identifying autistic youth who may be at higher risk of developing mental health problems. Established risk factors for mental health problems in neurotypical populations are relevant for understanding mental health in autistic youth. Lay abstract: Experiencing stressful life events, such as a parent having had serious illness, parental divorce, bullying and victimization, is known to increase risk for mental health difficulties in neurotypical children. However, few studies have looked at whether stressful life events have a similar impact in autistic youth and if any individual characteristics may moderate the impact of said life events. In this study, we tested whether in autistic children aged 7–11 years, exposure to family-level stressful life events predicted later mental health symptoms (and vice versa). We also tested whether associations between stressful life events and mental health symptoms differed depending on the child's level of cognitive flexibility. We found stressful life events only predicted internalizing symptoms (such as anxiety and depression) in children with clinically significant difficulties in cognitive flexibility (as rated by their parents). Mental health symptoms did not predict future exposure to stressful life events. Results suggest that information about exposure to stressful life events and cognitive inflexibility may be helpful in identifying autistic children who may be at risk of developing anxiety and depression symptoms.